Trends in investigations of abuse or neglect referred by hospital personnel in Ontario. Issue 1 (4th February 2019) - Fallon, Barbara; Filippelli, Joanne; Joh-Carnella, Nicolette; Miller, Steven P; Denburg, Avram
Abstract : Background: There is a dearth of literature surrounding mandated reporters to child welfare services in the Canadian context. This paper examines 20 years of reporting patterns from hospitals, which represent 5% of all referrals to child welfare services in Ontario. Methods: The Ontario Incidence Study of Reported Child Abuse and Neglect (OIS) is a representative study that has taken place every 5 years since 1993. The OIS is a multistage cluster sample design, intended to produce an estimate of reported child abuse and neglect in the year the study takes place. Results: There have been significant changes in referral patterns over time. Hospital referrals in 2013 are more likely to involve a concern of neglect, risk of maltreatment or exposure to intimate partner violence. In 1993, children were more likely to be referred from a hospital for a concern of physical abuse. Between 1993 and 1998, there was a significant drop in the number of sexual abuse investigations referred from a hospital. Hospitals have low rates of substantiation across all of the OIS cycles. Conclusion: This is the first study to examine hospital-based referral patterns in Canada. The relatively low percentage of hospital referrals across the cycles of the OIS is consistent with the extant literature. The findings warrant further discussion and research. This study is foundational for future research that can assist in identifying and developing responses across sectors that meet the complex needs of vulnerable families and that ultimately promote children's safety and well-being.